Can Vitamin D Supplementation in Addition to Asthma Controllers Improve Clinical Outcomes in Patients With Asthma?: A Meta-Analysis. Issue 50 (December 2015) - Luo, Jian; Liu, Dan; Liu, Chun-Tao
Abstract : Abstract: Effects of vitamin D on acute exacerbation, lung function, and fraction of exhaled nitric oxide (FeNO) in patients with asthma are controversial. We aim to further evaluate the roles of vitamin D supplementation in addition to asthma controllers in asthmatics. From 1946 to July 2015, we searched the PubMed, Embase, Medline, Cochrane Central Register of Controlled Trials, and ISI Web of Science using "Vitamin D, " "Vit D, " or "VitD" and "asthma, " and manually reviewed the references listed in the identified articles. Randomized controlled trials which reported rate of asthma exacerbations and adverse events, forced expiratory volume in 1 s (FEV1, % of predicted value), FeNO, asthma control test (ACT), and serum 25-hydroxyvitamin D levels were eligible. We conducted the heterogeneities test and sensitivity analysis of the enrolled studies, and random-effects or fixed-effects model was applied to calculate risk ratio (RR) and mean difference for dichotomous and continuous data, respectively. Cochrane systematic review software Review Manager (RevMan) was used to test the hypothesis by Mann–Whitney U test, which were displayed in Forest plots. Seven trials with a total of 903 patients with asthma were pooled in our final studies. Except for asthma exacerbations (I2 = 81%, χ2 = 10.28, P = 0.006), we did not find statistical heterogeneity in outcome measures. The pooled RR of asthma exacerbation was 0.66 (95% confidence interval: 0.32–1.37), but without significant difference (z = 1.12, P = 0.26), neither was in FEV1 (z = 0.30, P = 0.77), FeNO (z = 0.28, P = 0.78), or ACT (z = 0.92, P = 0.36), although serum 25-hydroxyvitamin D was significantly increased (z = 6.16, P < 0.001). Vitamin D supplementation in addition to asthma controllers cannot decrease asthma exacerbation and FeNO, nor improve lung function and asthma symptoms, although it can be safely applied to increase serum 25-hydroxyvitamin D levels.